2004
DOI: 10.1152/ajpgi.00221.2003
|View full text |Cite
|
Sign up to set email alerts
|

A new model of pacing in the mouse intestine

Abstract: A simple model of pacing in mouse intestine to longitudinal (LM) as well as circular muscle (CM) has been developed. Undissected segments of LM or CM from mouse ileum or jejunum were prepared to record contractions, nerve functions were inhibited, and regular spontaneous contractions were recorded. These had the properties expected of interstitial cells of Cajal (ICC) paced contractions: ileum slower than jejunum, inhibited but not abolished by nicardipine, reduced in frequency by cyclopiazonic acid, abolished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 58 publications
3
46
0
Order By: Relevance
“…However, examination of the applicability of these data to intact intestines remains an important question. We have demonstrated that pacing in undissected segments of mouse intestines after nerve block is similar in several respects to the pacing observed in cultured or dissected mouse intestines (4). Both exhibit TTX and L-type Ca 2ϩ channel independence, high temperature dependence, jejunum faster than ileum, and in W/W V intestine, lacking ICC-MP, CM is poorly active.…”
mentioning
confidence: 53%
“…However, examination of the applicability of these data to intact intestines remains an important question. We have demonstrated that pacing in undissected segments of mouse intestines after nerve block is similar in several respects to the pacing observed in cultured or dissected mouse intestines (4). Both exhibit TTX and L-type Ca 2ϩ channel independence, high temperature dependence, jejunum faster than ileum, and in W/W V intestine, lacking ICC-MP, CM is poorly active.…”
mentioning
confidence: 53%
“…Although Daniel et al (2002) reported the presence of cyclic mechanical activity (slower in the ileum than jejunum) in the longitudinal and circular muscle of the small intestine in the W/W V mutant mouse, we have recently shown that spontaneous electrical and mechanical activities of the longitudinal and circular muscle were significantly different between the ileum and jejunum in the W/W V mutant mouse (Nakagawa et al, 2003(Nakagawa et al, , 2005. Furthermore, we found that tight synchronicity between longitudinal and circular muscle contraction was present in the segments of jejunum and ileum even in the W/W V mouse.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that spontaneous rhythmic contractions are observed in the proximal colon of Ws/Ws rats, where there is a deficiency of both ICC in the myenteric region (ICC-MY) and of ICC-SM (Yoneda et al, 2001). Furthermore, it has been reported that smooth muscle preparations of the small intestine (duodenum, jejunum or ileum) of W/W V mutant mice show a variety of electrical activities (Malysz et al, 1996), longitudinal cyclic contractions (Daniel et al, 2002) and distension-induced peristalsis . In the small intestine of W/W V mutant mice, while ICC-MY are absent, the ICC of the deep muscular plexus region (ICC-DMP) are present (Malysz et al, 1996;Takayama et al, 2001Takayama et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…39 Similar findings were also reported in in vitro studies in ICC knocked out mice. 40,41 Because of its pacing capability, GES with long pulses is also able to induce tachygastria when delivered at a tachygastrial frequency (a frequency higher than the physiological frequency). 42,43 GES-induced tachygastria was reported to be associated with antral hypomotility, mediated via the adrenergic pathway.…”
Section: Alterations Of Gastric Slow Wavesmentioning
confidence: 99%